2022
DOI: 10.1111/nph.18380
|View full text |Cite
|
Sign up to set email alerts
|

A reactive oxygen species Ca2+ signalling pathway identified from a chemical screen for modifiers of sugar‐activated circadian gene expression

Abstract: Sugars are essential metabolites for energy and anabolism that can also act as signals to regulate plant physiology and development. Experimental tools to disrupt major sugar signalling pathways are limited. We performed a chemical screen for modifiers of activation of circadian gene expression by sugars to discover pharmacological tools to investigate and manipulate plant sugar signalling.Using a library of commercially available bioactive compounds, we identified 75 confident hits that modified the response … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Sugar promotes accumulation of superoxide and cytosolic Ca 2+ in both Arabidopsis and rice and acts to increase expression of circadian clock genes in the evening (Román et al, 2021;Chen et al, 2022;Li et al, 2022). Pharmacological inhibition of this superoxide-Ca 2+ signalling pathway in Arabidopsis lengthens circadian period (Li et al, 2022). We found that the same inhibitors also reduce the response the WRKY transcripts to sucrose (Fig 2), suggesting they are also activated by the superoxide-Ca 2+ pathway.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Sugar promotes accumulation of superoxide and cytosolic Ca 2+ in both Arabidopsis and rice and acts to increase expression of circadian clock genes in the evening (Román et al, 2021;Chen et al, 2022;Li et al, 2022). Pharmacological inhibition of this superoxide-Ca 2+ signalling pathway in Arabidopsis lengthens circadian period (Li et al, 2022). We found that the same inhibitors also reduce the response the WRKY transcripts to sucrose (Fig 2), suggesting they are also activated by the superoxide-Ca 2+ pathway.…”
Section: Discussionmentioning
confidence: 55%
“…Using qRT-PCR, we confirmed that these four genes were upregulated in response to sucrose, compared to mannitol controls in dark-adapted seedlings (Fig 2). Furthermore, we tested whether the induction of these genes by sucrose was inhibited by DPI or PI, two chemicals that inhibit a sugar-activated superoxide-Ca 2+ signalling pathway (Román et al ., 2021; Li et al ., 2022). Upregulation of all four WRKY genes by sugar was significantly inhibited by either DPI or PI (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Li et al . (2022) recently provided a new strategy and set of pharmacological tools to dissect signalling pathways that regulate plant growth. But most relevant to my current work, I am fascinated by the ongoing debate that wrestles on the polarising and controversial primary function and functional significance of anthocyanins in plants (Renner & Zohner, 2019; Pena‐Novas & Archetti, 2020; Agati et al ., 2021).…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Yea...mentioning
confidence: 99%
“…As someone who started in photobiochemistry, I also enjoyed reading the insightful Commentary by Professor Batschauer (2022) on two papers (Liu et al, 2022;Miao et al, 2022) regarding the stability and regulation of cryptochrome 1 in response to high light. Furthermore, Li et al (2022) recently provided a new strategy and set of pharmacological tools to dissect signalling pathways that regulate plant growth. But most relevant to my current work, I am fascinated by the ongoing debate that wrestles on the polarising and controversial primary function and functional significance of anthocyanins in plants (Renner & Zohner, 2019;Pena-Novas & Archetti, 2020;Agati et al, 2021).…”
Section: Why Did You Decide To Pursue a Career In Research?mentioning
confidence: 99%